Optimization of strength and ductility in nanotwinned ultra-fine grained Ag: Twin density and grain orientations. (1st September 2015) - Ott, R.T.; Geng, J.; Besser, M.F.; Kramer, M.J.; Wang, Y.M.; Park, E.S.; LeSar, R.; King, A.H.
Abstract: Nanotwinned ultrafine grained Ag thick films with different twin densities and orientations have been synthesized by magnetron sputtering with a wide-range of deposition rates. The twin boundary (TB) spacings and orientations as well as the grain size for the different deposition conditions have been characterized by both synchrotron X-ray scattering and transmission electron microscopy (TEM). Structural characterization combined with uniaxial tensile tests of the free-standing films reveals a large increase in the yield strength for films deposited at high deposition rates without any accompanying change in the TB spacing – a behavior that is not reported in the literature. We find that films deposited at lower deposition rates exhibit more randomly oriented grains with a lower overall twin density (averaged over all the grains) than the more heavily twinned grains with strong 〈1 1 1〉 fiber texture in the films deposited at higher deposition rates. The TB spacing in the twinned grains, however, does not show any significant dependence on the deposition rate. The dependence of the strength and ductility on the twin density and orientations can be described by two different soft deformation modes: (1) untwinned grains and (2) nanowinned grains that are not oriented with 〈1 1 1〉 along the growth direction. The untwinned grains provide relatively low resistance to slip, and thus decreased strength, while the nanotwinned grains that are not oriented with 〈1 1 1〉 along the growth direction are softer than nanotwinned grains that are oriented with 〈1 1 1〉 along the growth direction. We have revealed that an ultrafine-grained (150–200 nm) structure consisting of a mixture of nanotwinned (∼8–12 nm spacing) and untwined grains yields the best combination of high strength and uniform tensile ductility.